KONSEP KEHIDUPAN DUNIA AKHIRAT DAN IMPLIKASINYA TERHADAP PENDIDIKAN ISLAM - Suhendri; Andewi Suhartini (Sekolah Tinggi Agama Islam Al-Andina, 2024)
Differences in views regarding the concepts of “dunia” and akhirat” are due to differences in the epistemological basis used by the Western view and the Islamic view. This research aims to explain Islamic views on the concept of “dunia” and akhirat”, explain the consequences of faith in the last day, explain the concept of balance in world life and the afterlife, and explain the implications for Islamic education. The method used in this research is library research, namely exploring the opinions of Muslim commentators or scholars regarding the concepts of “dunia” and akhirat” which they interpret from the main sources, namely the Qur'an and al-Hadith. The results of the research state that Islam views “dunia” and akhirat” as having to be lived in balance. Life on earth is a field leading to the afterlife. This has implications for the concept of balance in the world and the afterlife, physical and spiritual, individual and society. It also has implications for the Islamic education system which combines and integrates general knowledge and religious knowledge that appears in various educational institutions. Conclusion; Islam's universal view of all aspects of life creates balance. The implications of the concept of balance in the afterlife in educational studies can be seen when Islamic education is present in providing challenges and answers to change as well as responses to development that suit the needs of the people.